Technical Efficiency of Private Clinics Under Universal Coverage Scheme in Bangkok, Thailand - Kanyang, Pimpitcha; Kraipornsak, Paitoon (Thammasat Review of Economic and Social Policy, 2021)
This study aims to measure the technical efficiency of 88 private clinics under Universal Coverage Scheme (UCS) in Bangkok for the fiscal year 2017 and to identify the factors affecting their technical efficiency. This cross-sectional study uses secondary data collected in fiscal year 2017 (October 2016- November 2017), from the database of National Health Security Office (NHSO). The study is divided in to two parts. The first part measures technical efficiency with data envelopment analysis (DEA) and the second part identifies the factors affecting efficiency with regression analysis using a Tobit model. The result of DEA under a variable return to scale assumption showed that 95.45 percent of the target study were operating on pure technical efficiency frontier (TEVRS), the mean pure technical efficiency score was equal to 0.98. Furthermore, the results of regression analysis revealed that only health supporting staff ratio was significantly affecting on pure technical efficiency (TEVRS) of private clinics under UCS.